To solve the inequality \(49x^2 - x^4 \geq 0\), we can start by rearranging it:
\[ -x^4 + 49x^2 \geq 0 \]
This can be rewritten as:
\[ x^4 - 49x^2 \leq 0 \]
Now, we can factor the left side:
\[ x^2(x^2 - 49) \leq 0 \]
Next, we can further factor \(x^2 - 49\) using the difference of squares:
\[ x^2(x - 7)(x + 7) \leq 0 \]
Now we will find the critical points by setting each factor to zero:
- \(x^2 = 0 \Rightarrow x = 0\)
- \(x - 7 = 0 \Rightarrow x = 7\)
- \(x + 7 = 0 \Rightarrow x = -7\)
Thus, the critical points are \(x = -7\), \(x = 0\), and \(x = 7\). These points divide the real number line into intervals:
- \((- \infty, -7)\)
- \((-7, 0)\)
- \((0, 7)\)
- \((7, \infty)\)
Next, we can test points from each interval to see where the expression \(x^2(x - 7)(x + 7)\) is less than or equal to zero.
-
Test a point in \((- \infty, -7)\), e.g. \(x = -8\): \[ (-8)^2(-8 - 7)(-8 + 7) = 64(-15)(-1) = 960 > 0 \]
-
Test a point in \((-7, 0)\), e.g. \(x = -1\): \[ (-1)^2(-1 - 7)(-1 + 7) = 1(-8)(6) = -48 < 0 \]
-
Test a point in \((0, 7)\), e.g. \(x = 1\): \[ (1)^2(1 - 7)(1 + 7) = 1(-6)(8) = -48 < 0 \]
-
Test a point in \((7, \infty)\), e.g. \(x = 8\): \[ (8)^2(8 - 7)(8 + 7) = 64(1)(15) = 960 > 0 \]
Now we summarize the test results:
- The expression is non-positive in the intervals \((-7, 0)\) and \((0, 7)\).
- We also include the points \(x = -7\), \(x = 0\), and \(x = 7\) since the original inequality is non-strict (i.e., \(\geq 0\)).
Thus, the solution in interval notation is:
\[ [-7, 0] \cup [0, 7] \]
Final Answer:
A. The solutions are the values of x in the interval \([-7, 0] \cup [0, 7]\).